FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN ON ASSETS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tjia, Cindy; Raymond (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The author decided the work of this research with the aim to search and analyzed the effect of the independent variables in this study were capital adequacy ratio (CAR), and loan to deposit ratio (LDR), the dependent variable return on assets (ROA). The object under this study were the banks that listed on the Indonesia Stock Exchange during 2015-2018 used as secondary data. The author decided to use type of causality research that was strung together to examine the probability of a relation resulting from and due to fellow independent variables and also the dependent variable. Used secondar data from the annual report got from the official website of the Indonesia Stock Exchange, www.idx.co.id. The purposive sampling method was the method used by the authors in the sample allowance. In accordance with the specified selection method, the authors managed to collect 44 banking samples. The results obtained in this research test was a significant between the capital adequacy ratio to return on assets, not significant between the loan to deposit ratio to return on assetss, but there is a significant effect between return on assets and loan to deposit ratio on return on assets as a simultaneous.